2012
DOI: 10.1177/039463201202500110
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell-Derived Microvesicles Improve Neovascularization in a Murine Model of Hindlimb Ischemia

Abstract: Paracrine mediators released from endothelial progenitor cells (EPCs) have been implicated in neoangiogenesis following ischemia. Recently, we demonstrated that microvesicles (MVs) derived from EPCs are able to activate an angiogenic program in quiescent endothelial cells by a horizontal transfer of RNA. In this study we aim to investigate whether EPC-derived MVs are able to induce neoangiogenesis and to enhance recovery in a murine model of hindlimb ischemia. Hindlimb ischemia was induced in severe combined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 35 publications
4
129
0
Order By: Relevance
“…In other situations, the injection of proangiogenic exosomes can be beneficial. For example, the previously mentioned vesicles isolated by Camussi et al 61 have been shown to induce neovascularization in a murine model of hindlimb ischemia, 72 stimulating angiogenesis by means of miRNA or mRNA transfer. 73 Protection was lost after RNAse treatment or depletion of proangiogenic miR-126 and miR-296.…”
Section: Exosomes and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…In other situations, the injection of proangiogenic exosomes can be beneficial. For example, the previously mentioned vesicles isolated by Camussi et al 61 have been shown to induce neovascularization in a murine model of hindlimb ischemia, 72 stimulating angiogenesis by means of miRNA or mRNA transfer. 73 Protection was lost after RNAse treatment or depletion of proangiogenic miR-126 and miR-296.…”
Section: Exosomes and Cvdmentioning
confidence: 99%
“…73 Protection was lost after RNAse treatment or depletion of proangiogenic miR-126 and miR-296. 61,72 Human cardiomyocyte progenitor cells have also been shown to release exosomes, which can stimulate the migration of microvascular endothelial cells. 74 In an interesting recent study, human umbilical vein endothelial cells subjected to shear stress were shown to release vesicles (exosomes or microvesicles) enriched in miR-143/145, which controlled target gene expression in cocultured smooth muscle cells.…”
Section: Exosomes and Cvdmentioning
confidence: 99%
“…The effects of endothelial progenitor cell MPs are associated with the PI3K/Akt signaling pathway and eNOS activation (59 ). Treatment with endothelial progenitor cell MPs improves neovascularization and favors regeneration in severe mouse hind limb ischemia, suggesting a possible use of these MPs for treatment of peripheral arterial disease (60 ).…”
Section: Mps Alter Endothelial Cell Survival and Angiogenesismentioning
confidence: 99%
“…Human progenitor ECs were shown to also release microvesicles containing miR-126, miR-296 and other angiogenic miRNAs (Deregibus et al, 2007). Microvesicles derived from these progenitor cells were capable to promote endothelial cell survival, proliferation, and organization in capillarylike structures in immunodeficient mice (Deregibus et al, 2007) and to induce neoangiogenesis and enhance recovery in a murine model of hindlimb ischemia (Ranghino et al, 2012). These observations suggest for a putative therapeutic potential of progenitor ECs as a source of microvesicles.…”
Section: Exosomes/microvesicles and Apoptotic Bodiesmentioning
confidence: 96%